If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -1 = 2x + 1 + 10 Reorder the terms: -1 + X = 2x + 1 + 10 Reorder the terms: -1 + X = 1 + 10 + 2x Combine like terms: 1 + 10 = 11 -1 + X = 11 + 2x Solving -1 + X = 11 + 2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + X = 11 + 1 + 2x Combine like terms: -1 + 1 = 0 0 + X = 11 + 1 + 2x X = 11 + 1 + 2x Combine like terms: 11 + 1 = 12 X = 12 + 2x Simplifying X = 12 + 2x
| a^2-14a+79=-8 | | 5p+23=35 | | 2x-29=21 | | 113c+c=1250 | | 10x+16=216 | | 62/x=16/12 | | -11x+17=-93 | | 5x=6+4x | | 4x+6-8x=26-4x | | .35x-y=1908 | | a^2+12ab+32b^2= | | 3x^2+30x-x^3=-48 | | 8x=3+7x | | 3.9(x-1.5)=24.18 | | 84-6n=36 | | 5.1x-5.5+7x=7.1x-17.5 | | .35x=1908 | | 2n-14=26 | | x^2+(2x+5)=20 | | 5(x-8)+8x=-31+4x | | .35xy=1908 | | n+13=42 | | 20(x+15)=5 | | 5-7x+15=5x+20-12x | | b^2+3b+9=0 | | 3x=2+2x | | x^2+2x+5=20 | | 2x(1+-3x)+-1+3x=0 | | 4x=4.5x+35 | | 2x(1-3x)-1+3=0 | | 8x+6=7x+13 | | X^2+6x+58=-4 |